Pemanfaatan Dana Desa Berbasis Perkembangan dan Resiliensi Desa di Kabupaten Pandeglang Provinsi Banten - Siti Khoeriyah; Ernan Rustiadi; Akhmad Fauzi Syam (Diponegoro University, 2020)
This study aimed at map village typologies based on the status of rural development and resilience for prepare the guidance village funds usage. Status of rural development was built with 13 indicators and status resilience was built with 10 indicators. The study used secondary data from BPS, wich was PODES 2014 in 326 villages at Pandeglang district. The results showed that 5 villages were categorized as advanced villages, 93 villages were categorized as developed villages, 177 villages as undeveloped villages, and 52 were categorized as outlying villages. Based on resilience status, there were 16 villages categorized as low resilience villages, 239 villages as middle resilence villages, and 71 villages categorized as high resilience villages. Based on the status of development and resileince, 4 villages were categorized as typology B (advanced and middle resilience villages), 1 village were typology C (advanced and low resiliece villages), 4 villages were typology D (developed and high resilience villages), 79 villages were typology E (developed and middle resilience villages), 9 villages were typology F (developed and low resilience villages), 35 villages were typology G (undeveloped and high resilience villages), 136 were typology H (undeveloped and middle resilience villages), 6 villages were typology I (undeveloped and low resilience villages), 32 villages were typology J (outlying and high resilience villages), and 20 villages were typology K (outlying and middle resilience villages)